ANALYSIS OF POST-PANDEMI ETHICS PRACTICES FOR FUTURE ACCOUNTANTS - Pratama, Bagas Brian (Klabat Accounting Review, 2024)
This study analyzes the threats to professional accountants' ethical practice in the new normal era after the Covid-19 pandemic. The method uses a literature study with four stages of analysis. First, is data collection using a literature study. Articles used as references use databases from ScienceDirect, Scopus, EBSCO, SINTA, and ProQuest which were published in 2020 to 2022 with the keywords "COVID-19" and "Accountant" and "ethic challenges" or "Issue Ethic" or "Professional" Ethics." The next step is compiling an information matrix to analyze the general picture regarding ethical conditions and changes due to the COVID-19 pandemic. The third stage is an in-depth analysis using two approaches: the first by comparative analysis and the second by conducting further analysis. The last stage is the conclusion stage. At this stage, a strategy is formulated to prepare future professional accountants to deal with ethical disruptions. The study results show that the Covid-19 pandemic creates multidimensional pressure, which results in future ethical practice changes. For this reason, professional accountants must prepare themselves to maintain ethical principles, especially integrity, objectivity, competence, prudence, professionalism, and confidentiality Keywords: Accountant Professional; Ethical Changes; Covid-19 Pandemic; New Normal Penelitian ini menganalisis ancaman yang terjadi pada praktik etika akuntan profesional dalam era kenormalan baru pasca pandemi covid-19. Metode penelitian menggunakan metode studi literatur dengan empat tahapan analisa. Pertama adalah pengumpulan data menggunakan studi literatur. Artikel yang dijadikan rujukan menggunakan data base dari Sciencedirect, Scopus, EBSCO, SINTA dan ProQuest yang terbit dalam pada tahun 2020 sampai 2022 dengan kata kunci “COVID-19” and “Accountant” and “ethic challenges” or “Issue Ethic” or “Professional Ethic”. Tahapan selanjutnya adalah menyusun matriks informasi untuk mendapatkan analisis gambaran umum terkait kondisi etis dan perubahan etika yang terjadi akibat pandemi covid-19. Tahapan ketiga adalah analisis mendalam dengan menggunakan dua pendekatan, yaitu pertama dengan analisa perbandingan (komparasi) dan kedua dengan melakukan analisa lanjutan. Tahapan terakhir adalah tahap kesimpulan. Pada tahapan ini dirumuskan strategi untuk menyiapkan akuntan profesional masa depan dalam menghadapi disrupsi etis yang terjadi. Hasil penelitian menunjukkan bahwa kondisi pandemi Covid-19 menimbulkan tekanan multidimensi yang berakibat pada perubahan praktek etis di masa depan. Untuk itu, akuntan profesional harus menyiapkan diri dalam menjaga prinsip etis khususnya integritas, objektivitas, kompetensi, kehati-hatian, profesionalisme, dan kerahasiaan. Kata kunci: Akuntan Profesional; Perubahan Etika; Pandemi Covid-19; Kenormalan Baru